A Pragmatic Analysis of Fallacies in English Religious Argumentative Discourse - Mahmood, Khawla Shukur; Ali, Sundus Muhsin (Al-Adab Journal, 2022)
Fallacies are common errors in an argument and they undermine the logic of that argument. They obstruct the process of argumentation since they do not contribute to the resolution in difference in opinion. The current study investigates fallacies in four religious argumentative debates between Muslims and atheists. It adopts Toulmin et al (1984) as a model for analysis. Results show that both debating parties, Muslims and atheists commit fallacies but the latter exceeds the former quantitatively and qualitatively. The most common fallacies in Muslims’ arguments are straw man argument, poisoning the well and attacking the person whereas the straw man argument, argument from ignorance, hasty generalization and appeal to compassion are the most committed ones by atheists.